Bony ankylosis of the facet joint of the cervical spine in rheumatoid arthritis: Its characteristics and relationship to the clinical findings. Issue 5 (3rd September 2017) - Iizuka, Haku; Iizuka, Yoichi; Okamura, Koichi; Yonemoto, Yukio; Mieda, Tokue; Takagishi, Kenji
Abstract: Objectives: The purpose of this study was to clarify the characteristics of bony ankylosis of the facet joint of the cervical spine in rheumatoid arthritis (RA) patients who required cervical spine surgery, and its relationship to the clinical findings. Methods: Eighty consecutive RA patients with cervical spine disorder who received initial surgery were reviewed. The occurrence of bony ankylosis of the facet joint of the cervical spine was investigated using computed tomography (CT) before surgery. We also evaluated the severity of neurological symptoms and the plain wrist radiographs taken before surgery; furthermore, we evaluated each patient's medical history for total knee arthroplasty (TKA) or hip arthroplasty (THA). Results: The preoperative CT imaging demonstrated bony ankylosis of the facet joint of the cervical spine in 45 facet levels of 19 cases (BA + group). In all patients, responsible instability or stenosis was demonstrated just caudal or on the cranial side of those bony ankylosis. Before surgery, the BA + group included significantly more patients showing severe cervical myelopathy ( p < 0.05), and significantly more cases showing progressed ankylosis in the wrist joint bilaterally ( p < 0.01). There were also significantly more patients who received two or more TKA or THA before the cervical spine surgery in the BA + group ( p < 0.01). Conclusions: Bony ankylosis of the facet joint of the cervical spine may be a risk factor of instability or stenosis at the adjacent disc level and severe cervical myelopathy. Furthermore, its ankylosis was demonstrated in RA patients with severe destroyed joints.